A non-uniform corrosion model and meso-scale fracture modelling of concrete. (June 2018) - Xi, Xun; Yang, Shangtong; Li, Chun-Qing
Abstract: Corrosion-induced concrete cracking is a significant durability problem for reinforced concrete structures. Considerable research has been carried out in the last few decades to understand and model the expansion mechanism of the corrosion products around the reinforcing bar and simulate the cracking behaviour of the concrete cover. In this paper, a new corrosion model based on non-uniform corrosion expansion is formulated and validated against experimental data. A meso-scale fracture model, consisting of aggregates, cement paste/mortar and ITZ, is established for the cases of both middle and side reinforcing bars. Under the developed corrosion and concrete fracture model, the cracking phenomena of the concrete cover are accurately simulated. It has been found that the non-uniform corrosion model can be used to express the realistic corrosion rust progression around the reinforcing bar, with the best accuracy. It has also been found that some microcracks occur before they are connected to form the dominating discrete crack which usually appears on the concrete surface. Moreover, the effects of the corrosion variables, as well as other key material and geometric parameters, on surface cracking of concrete are investigated.